2016
DOI: 10.1080/14992027.2016.1265157
|View full text |Cite
|
Sign up to set email alerts
|

Influence of well-known risk factors for hearing loss in a longitudinal twin study

Abstract: Pre-existing hearing loss can increase the risk of hearing impairment due to occupational noise exposure. An increased risk for NIHL was also seen in the group with exposures below 85 dB(A), a result that indicates awareness of NIHL should be raised even for those working in environments where sound levels are below 85 dB(A).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 156 publications
0
5
0
Order By: Relevance
“…NIHL as a result of occupational exposure affects 45 million people worldwide and is the most commonly reported occupational disease 21,22 . Exposure to an 85-dB TWA over 8 hours places an individual at an 8% excess risk of occupational NIHL, but even levels below the recommended 85-dB limit have been shown to increase the risk of NIHL 9,10,23 . Levels exceeding 85 dB permit even less exposure time to reach the permissible daily dose 9,10 .…”
Section: Discussionmentioning
confidence: 99%
“…NIHL as a result of occupational exposure affects 45 million people worldwide and is the most commonly reported occupational disease 21,22 . Exposure to an 85-dB TWA over 8 hours places an individual at an 8% excess risk of occupational NIHL, but even levels below the recommended 85-dB limit have been shown to increase the risk of NIHL 9,10,23 . Levels exceeding 85 dB permit even less exposure time to reach the permissible daily dose 9,10 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, in adults, Nondahl [42] between baseline smoking habits and the incidence of hearing loss at 500 to 3,000 Hz among 531 men, although with only 46 incident cases of hearing loss there may have been limited power to detect an association [43][44]. And Johnson's study [45] in a cohort of male twins, including 583 individuals (239 twin pairs and 105 individuals without their twin brother) also concluded that no increased risk for hearing loss was seen in smokers when compared to non-smokers.…”
Section: Discussionmentioning
confidence: 99%
“…12,15,16 In a similar vein, a longitudinal twin study in the occupational health literature has shown that consistent exposures of 75 to 85 dBA (less than the NIOSH recommended doses) led to increased risk of noise-induced hearing loss. 17,18 We postulated that otology/neurotology ORs and temporal bone labs are especially susceptible to high levels of noise, due to high-speed drilling and suction-irrigator use during otologic and neurotologic approaches, which might predispose to subclinical hearing impairment given recent discoveries. Therefore, we measured average and peak sound levels as well as sound frequency distribution in multiple surgical settings to examine the risk for noise-induced and hidden hearing loss, with an emphasis on translabyrinthine approach given the lengthier duration of drilling and suction-irrigation use.…”
Section: Introductionmentioning
confidence: 99%
“…12,15,16 In a similar vein, a longitudinal twin study in the occupational health literature has shown that consistent exposures of 75 to 85 dBA (less than the NIOSH recommended doses) led to increased risk of noise-induced hearing loss. 17,18…”
Section: Introductionmentioning
confidence: 99%